Assessment of the quality of information provided by Combined Radar Airspace Surveillance Systems - Свид, І. В.; Обод, І. І.; Мальцев, О. С.; Зарицький, В. І.; Prokopovich, I.; Titova, N.; Romaniuk, R.; Smolarz, A.; Turgynbekov, Y. (SPIE, 2022)
The structure of information support for the airspace control system based on combined radar surveillance systems has been substantiated and investigated. This makes it possible to improve the quality of the detection of air objects, as well as to assess the accuracy of the location of the detected air objects. As a result, this improves the quality of information support for decision-makers in the airspace control system.